Ginkgolic acid promotes inflammation and macrophage apoptosis via SUMOylation and NF-κB pathways in sepsis - Liu, Xinyong; Chen, Longwang; Zhang, Chen; Dong, Wei; Liu, Hongbing; Xiao, Zhong; Wang, Kang; Zhang, Yaolu; Tang, Yahui; Hong, Guangliang; Lu, Zhongqiu; Zhao, Guangju (Frontiers in Medicine, 2023)
Excessive inflammation and increased apoptosis of macrophages contribute to organ damage and poor prognosis of sepsis. Ginkgolic acid (GA) is a natural constituent extracted from the leaves of Ginkgo biloba, that can regulate inflammation and apoptosis. The present study aims to investigate the potential effect of GA in treating sepsis and its possible mechanisms. Here, a classic septic mice model and a lipopolysaccharide (LPS)-induced RAW 264.7 inflammation model were established. Cytokines in serum and culture supernatant were detected by ELISA, and the mRNA levels of them were examined by PCR. Hematoxylin and eosin (H&E) staining was performed to determine histopathological changes in liver, lung and kidney. Bacterial burden in the blood, peritoneal lavage fluids (PLFs) and organs were observed on Luria-Bertani agar medium. Flow cytometry and western blotting was used to detect apoptosis and the expression level of apoptosis related molecules, respectively. Moreover, the levels of SUMOylation were detected by western blotting. The activity of NF-κB p65 was assessed by Immunofluorescence staining and western blotting. The result showed that GA promoted inflammatory responses, reduced bacterial clearance, aggravated organ damage, and increased mortality in septic mice. GA increased apoptosis in peritoneal macrophages (PMs) and RAW 264.7 cells. Meanwhile, GA inhibited SUMOylation and increased the nuclear translocation of NF-κB p65 as well as its phosphorylation level. Collectively, GA promotes inflammation and macrophage apoptosis in sepsis, which may be mediated by inhibiting the SUMOylation process and increasing NF-κB p65 activity.